Sistem Informasi Monitoring Proyek Berbasis Website (Studi Kasus: PT Electronic Data Interchange Indonesia) - Tyastuti, Tantri Dwi; Matondang, Nurhafifah (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2024)
The 4.0 era of technology really supports companies to maximize work, one of which is in the form of project monitoring. The current condition of the ongoing project monitoring or monitoring process at PT Electronic Data Interchange Indonesia (EDII) still does not have its own system, so currently the project team at PT EDII in working on client project reporting still uses data storage via Google Drive and data processing. google sheet form, so that employees need more time in supervising project workers and reporting the progress of ongoing projects. The tool in question is in the form of a monitoring dashboard project or a project management information system specifically for PT EDII in monitoring and controlling projects in the form of website-based applications using the PHP programming language and the use of the MySQL database. This system aims for the monitoring team in working on ongoing projects in order to create good and structured work results in the appeal of company targets. In the analysis of system design using PIECES analysis and software development methods using the Waterfall method. The results of this study are the creation of a project monitoring system with features in the form of client data management, project work, and employee data management. Keywords : Information Systems, Project Monitoring, PHP, Waterfall